Lightweight and porous cellulose-based foams with high loadings of zeolitic imidazolate frameworks-8 for adsorption applications. (15th March 2019) - Ma, Shanshan; Zhang, Meiyun; Nie, Jingyi; Tan, Jiaojun; Song, Shunxi; Luo, Yanwei
Highlights: Biodegradable ZIF-8@CNF@cellulose foams were prepared by in situ green growth method. The ZIF-8 crystals significantly improved the adsorption ability of composite foams. The CNF immobilized ZIF-8 crystals and improved the mechanical strength of foams. ZIF-8@CNF@cellulose foams showed high adsorption capacity for gases and heavy metals. Abstract: The excess emission of toxic gases in atmosphere and heavy metal ions in drinking water is still a serious threat to human health. In this paper, a lightweight and porous zeolitic imidazolate frameworks-8@cellulose nanofiber@cellulose foam (ZIF-8@CNF@cellulose foam) with excellent gas adsorption and heavy metal ions removal properties was prepared using a simple in situ green growth method. The nitrogen adsorption property of ZIF-8@CNF@cellulose foam was 30 times higher than pure cellulose foam. Furthermore, the adsorption testing demonstrated that the composite foam showed high adsorption capacity for fluorescent dyes (24.6 mg g −1 for rhodamine B), heavy metal ions (35.6 mg g −1 for Cr (VI)) and organic solvents (45.2 g g −1 for DMF). Additionally, the ZIF-8/cellulose-based foam with 40 wt.% CNF exhibited an excellent mechanical performance, reaching a compressive strength value of 1.30 MPa. Herein, this work provides a feasible method to prepare ZIF-8@CNF@cellulose foam composite materials, which could adsorb gas molecules and heavy metal ions and show a great potential in atmosphere and water treatment.